STRATEGI PENGEMBANGAN OBJEK WISATA BUNTU SINGKI’ KABUPATEN TORAJA UTARA - Joi Matius; Ade Lisa Matasik; Abedneigo C. Rambulangi (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to design development strategies for the Buntu Singki’ Tourist Attraction in North Toraja Regency using the 4A approach (Attraction, Accessibility, Amenities, Ancillary) and SWOT analysis. This research applies a descriptive qualitative method with data collected through interviews, observations, and documentation. The results indicate that Buntu Singki’ has strengths in its religious attraction and scenic beauty but faces weaknesses in accessibility and supporting facilities. Opportunities include the growing interest in cultural and religious tourism, while threats arise from competition with other destinations and shifting tourism trends. Recommended strategies include improving basic facilities, optimizing digital promotion, developing additional attractions, and collaborating with local accommodations. Through the implementation of these strategies, it is expected that Buntu Singki’ will increase visitor numbers and strengthen its competitiveness as a leading tourist destination. Keywords: Development Strateg, Tourist Attraction, Buntu Singki’, 4A Approach, SWOT Analysis